Educational technologies in medical and health sciences education - Bridges, Susan; Chan, Lap-Ki 1964-; Hmelo-Silver, Cindy E. (Cham Springer, 2016)
This evidence-packed guide explores the growing importance of new technologies and situated learning in the vanguard of medical and health sciences education, backed by real-world clinical applications. Its dual emphasis on problem-based learning (PBL) and applied learning is reflected in the range of author perspectives, from understanding how technologies engage learners to implications for program design. Innovations covered range from wider and more targeted use of mobile devices and electronic medical records to video cases and virtual patients, in clinical contexts from family practice to specialized surgery. At the same time, chapters detail both the necessary hardware for putting these systems into place and the software needed to make them accessible to learners. Among the featured topics: Technology and group processes in PBL: An ethnographic study. What is real? Using problem-based learning in virtual worlds. Are Wikipedia articles reliable learning resources in PBL curricula? Utilizing mobile electronic health records in clinical education. Measuring emotions in medicine: methodological and technological advances within authentic medical learning environments. The deteriorating patient smartphone app: towards serious game design. Medical/health sciences educators and researchers in educational technology will look to Educational Technologies in Medical and Health Sciences Education to pinpoint current and future trends in an ever-important field.
Keywords: Educational Technology; Education, Medical -- methods; Allied Health Occupations -- education; Problem-Based Learning -- methods; Medical education -- Technological innovations